A trust evaluation model for web service with domain distinction. (1st January 2012) - Wu, Jian-bin
To realise commercial application of web service, research on its trust and reputation model should be raised into the agenda. After all, short of trust and reputation evaluation, web service will be trustless, which is not propitious for its development. Considering the feature of web service and existing trust and reputation evaluation methods, a trust evaluation model supporting domain distinction for web service is put up. The model measures trust and reputation of web service from two roles: requestor and provider. And its measuring content includes: service function and its QoS. To take more interest in recommendation of web service from similar domain, it combines domain factors as weighted average to compute recommendation trust. The simulation indicates that it works well on evaluation of trust even on the conditions of fake services and opinions disturbance.